Sensibilidad al refuerzo y al castigo e impulsividad en criminales muy violentos: una evaluación psicopatológica cualitativa a partir de varios sujetos condenados = Sensitivity to reinforcement and punishment, and impulsivity in very violent criminals : a qualitative psychopathological assessment from several individuals convicted - Pérez-Fernández, Francisco (Behavior & Law Journal, 2015)
Established with refractoriness to treatment and clinical interventions especially violent criminals undiagnosed disabling mental diseases, this paper aims to assess their degree of sensitivity to reinforcement and punishment, and impulsivity, and put both elements relative with other possible personality disorders. For this, we worked with a discrete sample of people currently serving sentences in Spanish prisons very violent crimes, being the basic condition of your selection is of killing at least two people in either the same event or events alternative. Our hypothesis is that the violent personalities characterized by high anxiety shows greater sensitivity to reinforcement and punishment to those more properly cutting other antisocial. However, we detected a clear cognitive bias control on standard tests validated for conventional population, but not for subjects with that special characteristics.